Testing k-value in k-fold Cross Validation of Forecasting Models for Time Series Analysis of G-spreads of Top-quality RUB Bonds - Latysh, E.; Koshulko, O. (Індуктивне моделювання складних систем, 2012)
The paper aims to find the best k-values for k-fold based model validity in a particular problem related to the forecasting of bond yields for pension funds investment strategy. The GS system and results of experiments are shortly described.